Zasady stosowania komór inhalacyjnych u dzieci - Emeryk, Andrzej; Doniec, Zbigniew; Mazurek, Henryk; Krenke, Katarzyna; Pirożyński, Michał; Sosnowski, Tomasz; Florkiewicz, Emil (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Experts of four scientific societies and the independent experts described the position paper concerning the role of inhalation chambers in inhalation therapy in children. This document is directed to all paediatricians and family doctors. We have reviewed the most important original and review papers, together with an analysis of the holding chambers market in the country. Recommendations containing indications and principles of the selection as well as methods of inhalation from these devices in children at different age were pointed out.